Bioinspired soft robots based on organic polymer-crystal hybrid materials with response to temperature and humidity - Yang, Xuesong (2023)
The capability of stimulated response by mechanical deformation to induce motion or actuation is the foundation of lightweight organic, dynamic materials for designing light and soft robots. Various biomimetic soft robots are constructed to demonstrate the vast versatility of responses and flexibility in shape-shifting. We now report that the integration of organic molecular crystals and polymers brings about synergistic improvement in the performance of both materials as a hybrid materials class, with the polymers adding hygroresponsive and thermally responsive functionalities to the crystals. The resulting hybrid dynamic elements respond within milliseconds, which represents several orders of magnitude of improvement in the time response relative to some other type of common actuators. Combining molecular crystals with polymers brings crystals as largely overlooked materials much closer to specific applications in soft (micro)robotics and related fields.